Early Events in Retinal Degeneration Caused by Rhodopsin Mutation or Pigment Epithelium Malfunction: Differences and Similarities - Di Pierdomenico, Johnny; García-Ayuso, Diego; Pinilla, Isabel; Cuenca, Nicolás; Vidal-Sanz, Manuel; Agudo-Barriuso, Marta; Villegas-Pérez, María P. (Frontiers in Neuroanatomy, 2017)
To study the course of photoreceptor cell death and macro and microglial reactivity in two rat models of retinal degeneration with different etiologies. Retinas from P23H-1 (rhodopsin mutation) and Royal College of Surgeon (RCS, pigment epithelium malfunction) rats and age-matched control animals (Sprague-Dawley and Pievald Viro Glaxo, respectively) were cross-sectioned at different postnatal ages (from P10 to P60) and rhodopsin, L/M- and S- opsin, ionized calcium-binding adapter molecule 1 (Iba1), glial fibrillary acid protein (GFAP), and proliferating cell nuclear antigen (PCNA) proteins were immunodetected. Photoreceptor nuclei rows and microglial cells in the different retinal layers were quantified. Photoreceptor degeneration starts earlier and progresses quicker in P23H-1 than in RCS rats. In both models, microglial cell activation occurs simultaneously with the initiation of photoreceptor death while GFAP over-expression starts later. As degeneration progresses, the numbers of microglial cells increase in the retina, but decreasing in the inner retina and increasing in the outer retina, more markedly in RCS rats. Interestingly, and in contrast with healthy animals, microglial cells reach the outer nuclei and outer segment layers. The higher number of microglial cells in dystrophic retinas cannot be fully accounted by intraretinal migration, but no signs of microglial proliferation were observed. The etiology of retinal degeneration determines the initiation and pattern of photoreceptor cell death and simultaneously there is microglial activation and migration, while the macroglial response is delayed. The actions of microglial cells in the degeneration cannot be explained only in the basis of photoreceptor death because they participate more actively in the RCS model. Thus, the retinal degeneration caused by pigment epithelium malfunction is more inflammatory and would probably respond better to interventions by inhibiting microglial cells.